Dialectics of Language in Mantra as a Form of Local Wisdom Malay Culture - Rian Hidayat; Yulia Nelfita; Aris Yulantomo (Departement of Mathematics Education, 2024)
Although there are many medical alternatives, but the public still very much believes in the power of mantra in terms of treatment. Mantras also have sentences that contain supernatural powers and are full of mysteries. Sometimes the words spell unknown meaning. But it will give rise to magical power when speaking his words regularly and rhythmically. Mantra is also a word or prayers composed of strange words that are considered to contain the power and power to achieve what humans wantThe meaning of mantras is found in the practice of daily life in Malay society. To explore this usage, this article begins with a description of the form of mantras used and the structure of mantras that are usually found in Malay society. With qualitative analysis, this paper presents the relevance of the mantra as local wisdom in its dialectics with the development of Islam in Malay society. The results of the analysis showed that mantra tradition in Malay society is part of oral tradition that has long been practiced before Islam. Religious elements can be seen in the oral tradition of mantras used by malay people.